Prevalence of and Risk Factors for Depression Among Older Persons 6 Months After the Lushan Earthquake in China: A Cross-Sectional Survey - Li, Lan; Reinhardt, Jan D.; Pennycott, Andrew; Li, Ying; Chen, Qian (Frontiers in Psychiatry, 2020)
Background Older persons are particularly vulnerable to the impact of earthquakes and are more likely to suffer from depression. Objectives We aimed to estimate the prevalence of depression, to compare the prevalence between disaster-affected and non-disaster affected areas, and to explore additional risk factors for depression 6 months after the Lushan earthquake. Design A cross-sectional study was conducted. Setting A magnitude 7.0 earthquake occurred in Lushan County, Ya’an Prefecture, Sichuan Province, on April 20, 2013. In total, 196 people were killed, and 11,470 were injured over 5 days. Participants A multistage cluster sampling strategy was used. A total of 1,509 older persons (aged 60 or older) participated. Methods The Geriatric Depression Scale-15, the University of California Los Angeles Loneliness scale, the Activities of Daily Living Scale, the Social Support Rating Scale, and the Family Apgar Index scale were used to evaluate symptoms of depression, loneliness, dependence with respect to activities of daily living, perceived social support, and family function, respectively. A generalized linear regression model and multiple logistic regression analysis were employed to identify risk factors for depression. Results Using a cutoff score of 8, the prevalence of depression was 29.16% in the hardest-hit disaster area, 29.06% in the hard-hit disaster area, 31.61% in the moderately-hit disaster area, 17.94% in the remote non-disaster area, and 12.28% in the neighboring non-disaster area. The prevalence was significantly higher in the disaster areas than in the non-disaster areas. Risk factors for depression included an educational level of elementary school or lower, a greater number of chronic illnesses, feelings of loneliness, limitations in activities of daily living, family dysfunction, and low levels of social support. Conclusion Depression was highly prevalent in elderly survivors and was significantly more prevalent in disaster areas than in non-disaster areas. Psychological interventions and care should focus on older survivors.